2021
DOI: 10.1186/s12909-021-03010-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of research productivity during postgraduate medical education: a structured review

Abstract: Background Although formal participation in research is an integral and often mandatory component of clinical training programs, resulting productivity is highly variable. The objective of this review was to identify determinants of successful research performance among graduate medical education trainees. Methods A structured review of the published literature was performed by searching PubMed, CINAHL, and EMBASE from inception through to 7 April,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…Early exposure to research [18] may also increase the number of physician scientists [17,19]. Furthermore, residency training programs with organized programs/curricula, including protected time for research, were associated with increased productivity [20].…”
Section: Discussionmentioning
confidence: 99%
“…Early exposure to research [18] may also increase the number of physician scientists [17,19]. Furthermore, residency training programs with organized programs/curricula, including protected time for research, were associated with increased productivity [20].…”
Section: Discussionmentioning
confidence: 99%
“…Improved quality of evidence is a key target for further work. While formal quality assessment was not conducted, the vast majority of studies which used a comparator were pre-post studies, a nding re ected in similar reviews (Laupland, Edwards & Dhanani, 2021;Li et al, 2022;Stevenson et al, 2021). This design is vulnerable to bias, especially as very few of these studies determined the trajectory of their outcome measure prior to introducing the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been increased attempts to synthesise this evidence to determine which strategies may be most effective. Previous reviews have focused on residents speci cally (Laupland, Edwards & Dhanani, 2021; Noble et al, 2018; Stevenson et al, 2021), were restricted by location, type of strategy or outcome measure (Laupland, Edwards & Dhanani, 2021; Li et al, 2022;Stevenson et al, 2021), or also included the effect of nonmodi able factors, such as gender and seniority (Laupland, Edwards & Dhanani, 2021). To date, no reviews have systematically summarised the evidence on strategies affecting research engagement of medical practitioners more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…It is effective communication that will alleviate misunderstanding and disconnect between each other [ 36 ]. Findings on first-year nursing postgraduates and other medical postgraduates also showed that graduate students were more likely to achieve higher performance when they received high levels of support from their mentors [ 15 , 37 ]. First-year postgraduates expect mentors to take a leadership role, while second-year postgraduate students seem to be more willing to have continuous interaction and communication with their mentors.…”
Section: Discussionmentioning
confidence: 99%